Calcium Fluxes in Work-Related Muscle Disorder: Implications from a Rat Model. (30th September 2019) - Hadrevi, J.; Barbe, M. F.; Ørtenblad, N.; Frandsen, U.; Boyle, E.; Lazar, S.; Sjøgaard, G.; Søgaard, K.
Abstract : Introduction . Ca 2+ regulatory excitation-contraction coupling properties are key topics of interest in the development of work-related muscle myalgia and may constitute an underlying cause of muscle pain and loss of force generating capacity. Method . A well-established rat model of high repetition high force (HRHF) work was used to investigate if such exposure leads to an increase in cytosolic Ca 2+ concentration ([Ca 2+ ]i ) and changes in sarcoplasmic reticulum (SR) vesicle Ca 2+ uptake and release rates. Result . Six weeks exposure of rats to HRHF increased indicators of fatigue, pain behaviors, and [Ca 2+ ]i, the latter implied by around 50–100% increases in pCam, as well as in the Ca 2+ handling proteins RyR1 and Casq1 accompanied by an ∼10% increased SR Ca 2+ uptake rate in extensor and flexor muscles compared to those of control rats. This demonstrated a work-related altered myocellular Ca 2+ regulation, SR Ca 2+ handling, and SR protein expression. Discussion . These disturbances may mirror intracellular changes in early stages of human work-related myalgic muscle. Increased uptake of Ca 2+ into the SR may reflect an early adaptation to avoid a sustained detrimental increase in [Ca 2+ ]i similar to the previous findings of deteriorated Ca 2+ regulation and impaired function in fatigued human muscle.